Influence of personal relationships to conflict - Hasanov, H.; Sultanova, R. (Економічний вісник Донбасу, 2018)
In this research document main theories of culture are investigated, based on which it will be explained how personal relationships can play a vital role in management of conflicts. International approaches to conflict resolution were investigated and the information received was systematically analysed and presented as an instruction that can be used to manage hotel facilities as well as with other industrial enterprises. However, it is important to note that most managers may face a number of serious problems in their workperformance, because they do not know vital role of personal cultural backgrounds. From this point of view, the article is a scientific novelty in terms of explanation of the concept of conflict, solving its problems and conducting awareness-raising work on this topic.